Mendorong Prestasi Anak Dalam Tahfidz Qur'an: Peran Orang Tua Dalam Pembentukan Fondasi Keagamaan - Said, Ashim Ibrahim; Danang Dwi Basuki; Budianto (STAI AL-AMIN, 2024)
There are still many children who are unable to read the Qur'an today, one of the factors in this occurrence is because the child is not touched by Qur'anic learning. This can happen because the parents themselves do not understand the importance of reading the Qur'an. This study aims to determine the role of parents in memorizing the Koran of children in the formation of religious foundations. The research method used is descriptive qualitative method. The results showed that the role of parents in encouraging children's achievement in memorizing the Qur'an in XYZ District is very significant and diverse. They not only act as the first madrasah to teach religious values and praiseworthy morals from an early age, but also build a supportive home environment by setting special time for tahfidz and involving the whole family in religious activities.